The Role of Deontic Modality in Constructing Dystopian Fiction: A Cognitive Stylistic Analysis of Orwell’s 1984 - Khulaif Saad, Salim; Qasim Zaboon, Mohammad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This research analyzes the influence of deontic modality as one of the linguistic world-building tools of the dystopian text world in George Orwell’s 1984 (1949) within the framework of cognitive stylistics. Based on Simpson (1993) on modality framework, the research examines how the linguistic expressions of obligation, prohibition, and permissions serve as a control and ideological justification mechanism in the novel. The analysis shows how Orwell’s use of deontic modality goes beyond actions and encompasses thoughts, feelings, and perceptions, forcing the thorough internalization of the obedience. Through the analysis of the passages of 1984, the research shows the use of modal verbs like must, should, and was to be as a means of encoding ideological imperatives, move control to self-preoccupation as well as blur the distinction between external and internal control. The research concludes that the deontic modality impacts the cognitive framework of the reader concerning the presentation of authority, control, and resistance, so that, illustrating how language constructs and maintains a totalitarian grip on Orwell’s dystopian world. DOI: https://doi.org/10.54633/2333-024-057-002